2022
DOI: 10.1177/01632787221126500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacists’ Preferences and Barriers to Access Continuing Education: A Cross-Sectional Study in Lebanon

Abstract: The implementation of continuing education programs for pharmacists in Lebanon is emerging and needs to be further developed and strengthened to fill the gaps between knowledge acquisition and its application in the workplace. This study examined the perceptions of pharmacist preferences for and barriers to access programs. A crosssectional descriptive study was undertaken with a convenience sample of 142 pharmacists who were surveyed in their workplace. Almost 83.1% of pharmacists reported their day-to-day wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…As regards the clinical patterns of migraine, the average reported number of migraine days per month was 7.6 ± 9.6 with no significant association with the sex of the students in contrast with a study in 2018 where migraine frequency was higher among men. 32 Most of the migraine students had moderate (61.9%) and severe (32.6%) pain in comparison with a cross-sectional study carried out in Kuwait among medical students where 57% and 28.3% of students had a moderate and severe intensity of pain respectively. 33 In our study, a higher onset was reported during midday and night in coherence with the temporal patterns of migraine reported in a cross-sectional infodemiology study with the highest peak observed at 22h.…”
Section: Discussionmentioning
confidence: 80%
“…As regards the clinical patterns of migraine, the average reported number of migraine days per month was 7.6 ± 9.6 with no significant association with the sex of the students in contrast with a study in 2018 where migraine frequency was higher among men. 32 Most of the migraine students had moderate (61.9%) and severe (32.6%) pain in comparison with a cross-sectional study carried out in Kuwait among medical students where 57% and 28.3% of students had a moderate and severe intensity of pain respectively. 33 In our study, a higher onset was reported during midday and night in coherence with the temporal patterns of migraine reported in a cross-sectional infodemiology study with the highest peak observed at 22h.…”
Section: Discussionmentioning
confidence: 80%
“…Although an online survey was employed to improve dissemination, a satisfactory response rate was reported (46.9%), 20 but significantly lower than the one reported among community pharmacists in the period before the pandemic. 21 , 22 This can be related to the extension of the role of community pharmacists during the pandemic, such as authorization to prepare hand and surface disinfectants, promoting preventive measures to cope with the virus spread, and preparing compounding formulations in the pharmacy. 23 Moreover, the supplementary workload to mitigate drug shortage, provide support in the therapeutic procedure of patients, and focus on those requiring professional attention with symptoms not related to the pandemic limited pharmacists’ access to social platforms.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Other personal reasons could have affected the involvement of pharmacists, such as fear, anxiety, and lack of training on mental health and other challenges imposed by the COVID-19 outbreak. 21 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Most patients reported that doctors explained their medication plan, but not all understood it. This can partially explain the moderate awareness of patients about T2D and call for the need to provide workshops tailored for patient education [20], and include it in the continuing education program of healthcare providers [21,22]. Almost 45% of patients postponed their medical appointments, which can exacerbate diabetes complications and highlight the need for strict lifestyle and behavioral interventions [23].…”
Section: Discussionmentioning
confidence: 99%